Main aspects of personalized approach to the treatment of patients with chemotherapy resistant metastatic colorectal cancer - O. Yu. Stukalova; R. V. Ishchenko; A. A. Polikarpov; A. I. Farmonkulova (Южно-Российский онкологический журнал)
Purpose of the study. To improve the results of treatment of patients with unresectable metastases of colorectal cancer in the liver that are not controlled by systemic chemotherapy.Materials and methods. The study includes clinical data on the treatment of 76 patients with metachronous metastases of colorectal cancer in the liver that are not controlled by systemic chemotherapy. Patients underwent removal of the primary tumor according to urgent indications at the first stage of complex treatment, followed by systemic chemotherapy in an adjuvant mode. After 24.5 ± 0.2 months, patients were diagnosed with metastatic liver damage, and therefore systemic chemotherapy was initiated. After changing two lines of drug therapy with a registered progression of the oncological process, liver metastases were recognized as uncontrolled by systemic chemotherapy. After that patients were included in the given study and divided into two groups. The study group included 40 patients who underwent regional chemotherapy. The control group included 36 patients who continued systemic chemotherapy with subsequent line changes. The effectiveness was evaluated according to the RECIST 1.1 and mRECIST scales, as well as the overall one-year, two- and three-year survival rates.Results. The median overall survival of patients in the control and study groups was 30.0 ± 0.8 and 41.5 ± 0.5 months, respectively, p < 0.05. The total one-year, two- and three-year survival of patients in the control and study groups was 94.4 %, 69.4 %, 33.3 % and 100 %, 82.5 %, 57.5 %, respectively, p < 0.05. The median life expectancy of deceased patients in the control and study groups was 22.5 ± 0.4 and 27.0 ± 0.4 months.Conclusions. As a result of a comparative analysis of the detection of adverse events and complications of the treatment, patients of the study group underwent treatment much easier than patients of the control group – in patients in the group of systemic chemotherapy, moderate and severe complications were detected in 44.4 % of cases, in the study group – in 2.5 % of cases. According to the results of a clinical study, regional chemotherapy is an effective method of treating patients with colon cancer metastases in the liver that are not controlled by systemic chemotherapy and is associated with a statistically significant increase in overall survival (p < 0.05). For a more detailed study of the benefits of regional chemotherapy in this category of patients, further prospective clinical studies are necessary.